Respuesta :

Ok so first we have to solve for x


The value of x is already given in the equation x = y - 5


Than we plug in the value of x into the second equation so that only one variable is present to find the numerical value of y. (By the way y - 5 = -5 + y, I just reordered the equation to make it easier for me)


11(y - 5) - y = -25

11y - 55 - y = -25

10y - 55 = -25

10y = +30 (here I added +55 to both sides to isolate the variable)

y = 3(here I divided each side by 10 to truly isolate the variable and to find the value of y)


Now we plug in y = 3 into the first equation


x = y - 5

x = 3 - 5

x = -2


Therefore, x = -2 and y = 3




Hope this helps!

Answer:

x = -2 and y = 3

Step-by-step explanation: